Japan's Policy regarding the Israeli-Palestinian conflict: Balancing divergent interests and strategic constraints (2023–2024) - M. P. Chizhevskaya (Японские исследования)
The article examines Japan's policy towards the Israeli-Palestinian conflict in the aftermath of the Hamas attack on Israel on October 7, 2023. A core dilemma in Japan's approach lies in balancing its loyalty to Arab nations – crucial for securing energy supplies and avoiding a repeat of the 1973 "oil shock" – with its alignment to the United States' pro-Israel stance. These conflicting priorities make Japan's diplomatic behavior in this context particularly significant.